2002
DOI: 10.1074/jbc.m106643200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression of the Anti-apoptoticsurvivin Gene by Wild Type p53

Abstract: Survivin is a member of the inhibitor of apoptosis family. This apoptosis inhibitor also has an evolutionarily conserved role as a mitotic spindle checkpoint protein. Previous studies on p53-repressed genes have implicated several genes involved in the G 2 /M transition of the cell cycle as targets of negative regulation by p53. However, few targets of p53 repression that are antiapoptotic have been identified. This study identifies the anti-apoptotic survivin gene as a p53-repressed gene. Notably, Survivin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
597
2
14

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(661 citation statements)
references
References 50 publications
46
597
2
14
Order By: Relevance
“…46,47 Similarly, we also found that CDDP treatment reduced survivin expression in cells in which it did not activate Akt, including A549 NSCLC, and ZL5 and ZL34 MPM cells (Fig. 3d and data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…46,47 Similarly, we also found that CDDP treatment reduced survivin expression in cells in which it did not activate Akt, including A549 NSCLC, and ZL5 and ZL34 MPM cells (Fig. 3d and data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…31 Human survivin is negatively regulated by wild-type p53. 35,50,51 After DNA damage caused by chemotherapy, expression of wild-type p53 is upregulated, expression of survivin is downregulated, and cell-cycle arrest and apoptosis occur. Cells that express mutant p53 do not show these effects after chemotherapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of genes, including those identified by our group, that are induced by p53 have been isolated and well characterized so far. In addition, many genes that are negatively regulated by p53 such as Survivin, CDC2 and CDC25C have been reported (Taylor et al, 2001;Hoffman et al, 2002). However, the biological significance of genes repressed by p53 is still largely undisclosed.…”
Section: Introductionmentioning
confidence: 99%